Sulcus-Deepening Trochleoplasty for Trochlear Dysplasia - Anthony J. Ignozzi BS; Zane Hyde MD; Scott E. Dart MD; David R. Diduch MD (SAGE Publishing, 2021)
Background: Patients who are refractory to initial management of trochlear dysplasia, which consists of bracing and physical therapy, may be candidates for trochleoplasty. Indications: Indications for trochleoplasty include Dejour classification type B or D trochlear dysplasia, supratrochlear spur height ≥7 mm, and a positive J sign on examination. Technique Description: The thick shell sulcus-deepening trochleoplasty technique involves removing the supratrochlear spur by creating a 5-mm-thick osteochondral shell with underlying cavity, dividing the thick shell into medial and lateral leaflets, and securing the leaflets with absorbable sutures. This establishes a new trochlear groove that is flush with the anterior cortex of the femur. Results: A review of 21 studies with length of follow-up from 8.8 months to 15 years found postoperative dislocation was present in 0% to 15% of patients and the patient satisfaction ranged from 81.0% to 94.4%. A prospective study with a minimum 2-year follow-up found no cases of recurrent dislocation, no progression of radiographic arthritis, 84.8% of patients returned to sport, and the patient satisfaction was a 9.1/10. Discussion/Conclusion: Sulcus-deepening trochleoplasty for trochlear dysplasia provides patellar stability and excellent patient satisfaction.